Exploring Barriers of Teamwork in Providing Rehabilitation Services: A Qualitative Content Analysis - Parisa Jahanbin; Kianoush Abdi; Mohammad Saeed Khanjani; Mohammad Ali Hosseini (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Teamwork is a fundamental part of medical rehabilitation. The purpose of rehabilitation teamwork programs aims to enhance the functional and mental capabilities of disabled people to improve their quality of life. One of the problems of providing rehabilitation services in Iran is teamwork. In fact, teamwork is a missing link in rehabilitation services, and teamwork between physicians and therapists in different areas of rehabilitation helps to provide quality rehabilitation services. Therefore, this study aimed to identify barriers to teamwork in providing rehabilitation services. Materials & Methods This study was conducted in a qualitative approach to identify the barriers of teamwork using conventional content analysis based on Graneheim method (2004) in Shiraz and Tehran in 2017. 32 participants were selected based on purposive sampling with maximum diversity and sampling until data saturation. Data were collected through semi-structured interviews. Before the interview, the purpose of the study was explained and informed consent was obtained from the participants. Interviews lasted between 20 and 60 minutes and MAXQDA 10 software was used for data analysis. In this study, four criteria of acceptability, reliability, transferability and verification capability of Guba and Lincoln were used to evaluate and validate the data. Results After conducting interviews and analyzing of data, 846 primary codes extracted by removing similar codes. The classes were identified from the indirect open coding process by reading the text several times and assigning related codes to them by continually comparing the codes with each other and ensuring the accuracy of the coding. The findings of this study showed that the barriers to teamwork in providing rehabilitation services included a core theme of "trustworthy of a missing link to rehabilitation teamwork", and six main categories including: "disorderly planning and planning", "poor communication and coordination", " Lack of financial resources, "inadequate education system", "false cultural beliefs", "inadequate knowledge and experience", as well as 20 subcategories.. Conclusion According to the findings, efficient rehabilitation teamwork requires a comprehensive understanding, considering the long-term in addressing the barriers. Identifying the barriers for providing rehabilitation teamwork can be the first action in the formation and advancement of teamwork at hospitals and rehabilitation centers. The "trustworthy of a missing link to rehabilitation teamwork" was the main barrier to teamwork. The results of this study can provide insights and extensive knowledge about teamwork to policy-makers, managers, providers, and rehabilitation staff for removing these barriers to order promotion of rehabilitation services. Therefore, it is vital for health policy-makers and managers to change their vision and focus on teamwork as a key part of health plans. Further research is suggested.